Establishing a Comprehensive Tinnitus Care Pathway—Part 1: Essential Components - Zitelli, Lori; Alscher, Emma (Seminars in Hearing, 2024)
This article is the first in a two-part series intended to provide guidance related to the essential components of establishing a tinnitus care pathway in your clinic. Please see Part 2: Implementation for Additional Details Related to Implementation of the Suggested Protocols.
Keywords: tinnitus; clinical; implementation; pathway